Groundwater flow regime and quality assessment of the alluvial aquifer in the deltaic environment of river Pinios (Thessaly) - Matiatos, J.; Paraskevopoulou, V; Dassenakis, M.; Alexopoulos, J.; Panagopoulos, A; Lazogiannis, K.; Poulos, S.; Arampatzis, G; Ghionis, G.; Kotsopoulos, S; Botsou, F; Teou, X; et al. (10th International Hydrogeological Congress of Greece, 2014)
This study aims at defining the groundwater flow regime and the principal hydro-geochemical processes controlling groundwater quality in the deltaic plain of River Pinios (ThessalyGreece) and investigating whether seawater intrusion and pollution are influencing groundwater quality. Groundwater level monitoring from October 2012 to September 2013 shows that groundwater flow is seawards and that the water table of the phreatic aquifer is mainly declining during the summer period when it is over-pumping and natural recharge limited. Major ions analysed in 49 groundwater samples reveal that groundwater is mainly affected by four factors: (i) dissolution of calcite and dolomite; (ii) weathering of silicate minerals; (iii) seawater intrusion; and (iv) contaminant enrichment (e.g., NH4) mainly caused by point sources of pollution. High enrichment of Na and Cl near the coast gives an indication of seawater intrusion into the aquifer as also supported from the Na–Cl signature on the Piper diagram and the Revelle coefficient. The dissolution of calcite and dolomite results in Ca–HCO3 and Mg–HCO3 groundwater types, whereas natural geochemical processes are considered responsible for the aquifer's enrichment in minor elements (e.g., Fe, Mn). Based on the simulation results performed using PHREEQC model, groundwater is mainly supersaturated with respect to calcite and dolomite minerals, supporting a long residence time hypothesis. The relation between seasonal water level fluctuation and hydrochemistry shows that both are mainly controlled by the aquifer's recharge process.